Promotion effects of iron in carbon nanotubes synthesis to make supports for Fischer-Tropsch synthesis catalysts - Kente, Thobeka (My University, 2011)
Iron (Fe), catalysts were prepared by incipient wetness impregnation method using CaCO3 as a supporter. 0.6% Cu, 0.4% K, 0.6% Cu/0.4% K, 0.1 ml of Tetraethyl orthosilane (TEOS) in 2ml water were used as promoters for the Fe catalysts. The promoted catalysts were then employed in the synthesis of carbon nanotubes (CNTs) using a chemical vapor deposition (CVD) method. Transmission electron microscopy (TEM) revealed that Cu increased the diameter of the CNTs and caused them to be coiled, thereby altering the shape of the CNTs. The addition of K resulted in no recognizable change in the microstructure of these tubes. The CNTs obtained looked similar to those obtained when Fe was used without a promoter. However, the diameter of the tubes also increased due to K addition. Thermol Gravimetric Analysis (TGA) results showed that the addition of K to the Fe catalyst (Figure 20, p56, 57) resulted in the enhancement in thermal stability of the CNTs. BET analysis revealed that Cu increased the surface area while K decreased the surface area of this solid material. The Cu/K promoted catalyst produced CNTs with diameters of 60 nm which was the same as unpromoted catalyst. However, the CNT diameter distribution was quiet different for the two catalysts. The surface area was less than that of the unpromoted catalyst. The Fe/Cu/K synthesized CNTs were coiled and they looked more like the product produced from Fe/Cu CNTs. Thus the Cu catalyst has the dominant effect in determining the CNT morphology. When SiO2 was used as a promoter no change in the diameter distribution of the CNTs could be detected. Thus while changes to the carbon surface may have occurred at the atomic level, the changes were not detected at the TEM resolution used. The surface area was also less than that of CNTs produced over the unpromoted catalyst. Both promoted and unpromoted Fe/CNT were tested for FT synthesis. The activity, selectivity and CO conversions were recorded. The K was found to strongly influence the production of the hydrocarbon yield and increased the CO conversion. The K promoted catalyst increased the CO reaction rate, and increased the olefinity and the alpha value. The effect of K on the olefinity of the C2 hydrocarbon ranged from 0.04 to 0.26. An increase in FTS activity is also observed for the K promoted catalyst. Cu decreased the reduction temperature of Fe oxides as noted by TPR studies. The Cu promoted catalyst showed a high selectivity to methane and a decrease of C5+ hydrocarbons, the C2 olefins also decreased.